ANDROID-BASED LEARNING MEDIA DESIGN FOR INTRODUCTION TO SUNDA CULTURE FOR EARLY CHILDREN - Taopik Rahman; Silmi Qurota Aeni (Journal of Early Childhood Education (JECE), 2021)
This research aims to develop android-based learning media which aims to make children know Sundanese culture in a more effective, fun, and innovative way to introduce culture from an early age and can help the role of teachers or parents in educating and providing knowledge to children -children outside the school environment in a fun way. This research uses the Design Based Research (DBR) method for the Sunda Exploration Learning Media by carrying out four steps, namely the identification and problem analysis steps by researchers and practitioners collaboratively, developing a prototype solution based on theoretical benchmarks, existing design principles and technological innovations, conducting iterative process to test and improve practical solutions, reflections to produce design principles and improve implementation of practical solutions, Sundanese Exploration Learning Media can be used in learning with cultural themes. This media was developed based on the 2013 PAUD curriculum and adapted to the needs in the field regarding the fulfillment of Sundanese cultural learning. Based on the entire research process that has been carried out, the product designed by the researcher can be applied to early childhood education learning. In addition, the product can also be easily applied by teachers and parents, because this media is presented complete with a user guide ebook that describes the explanation and how to use it. Android-based learning media is the most effective media that can be one of early childhood learning in learning something. This learning media can be used by parents and schools, schools can use this application as additional learning and parents can use this application at home or anywhere.